Fecal Microbiomes in Premature Infants With and Without Parenteral Nutrition–Associated Cholestasis. Issue 2 (August 2019) - Mokha, Jasmeet S.; Davidovics, Zev H.; Maas, Kendra; Caimano, Melissa J.; Matson, Adam
ABSTRACT: Introduction: Premature infants often require parenteral nutrition (PN) until they reach enteral autonomy which puts them at risk of developing PN-associated cholestasis (PNAC). We sought to compare longitudinal changes in fecal microbiomes of premature infants who developed PNAC versus those who did not despite being on similar PN doses. Methods: Stool samples from premature infants (gestational age <30 weeks) who developed direct bilirubin ≥1.5 mg/dL while receiving PN were classified as precholestasis, cholestasis, or postcholestasis based on bilirubin levels at the time of sample acquisition and were compared to matched control groups 1, 2, and 3, respectively. Results: A total of 102 fecal samples from 8 cases and 10 controls were analyzed. Precholestasis samples were more abundant in phylum Firmicutes and genus Staphylococcus, whereas control 1 was more abundant in phylum Proteobacteria and genus Escherichia-Shigella . Nonmetric multidimensional scaling ordination plots based on the taxonomic composition of early fecal samples revealed significant separation between cases and controls. On indicator species analysis, genus Bacilli was more prevalent in samples from the precholestasis group, whereas genus Escherichia-Shigella was more prevalent in control 1. With feeding advances, weaning of PN and resolution of PNAC, most differences in microbiota resolved with the exception of control 3 group being more diverse compared to the postcholestasis group. Conclusions: Premature neonates who develop PNAC, compared to those who do not, show significantly different fecal microbiomes preceding the biochemical detection of cholestasis. Abstract : Supplemental Digital Content is available in the text